Reduced auditory evoked gamma band response and cognitive processing deficits in first episode schizophrenia. (18th August 2015) - Leicht, Gregor; Andreou, Christina; Polomac, Nenad; Lanig, Clarissa; Schöttle, Daniel; Lambert, Martin; Mulert, Christoph
Abstract: Objectives. Gamma-band oscillations (e.g., the early auditory evoked gamma-band response, aeGBR) have been suggested to mediate cognitive and perceptual processes by driving the synchronization of local neuronal populations. Reduced aeGBR is a consistent finding in patients with schizophrenia and high-risk subjects, and has been proposed to represent an endophenotype for the illness. However, it is still unclear whether this reduction represents a deficit in sensory or cognitive processes, or a combination of the two. The present study investigated this question by manipulating the difficulty of an auditory reaction task in patients with first-episode schizophrenia and healthy controls. Methods. A 64-channel EEG was recorded in 23 patients with first-episode schizophrenia and 22 healthy controls during two conditions of an auditory reaction task: an easy condition that merely required low-level vigilance, and a difficult condition that placed significant demands on attention and working memory. Results . In contrast to healthy controls, patients failed to increase aeGBR power and phase-locking in the difficult condition. In patients, aeGBR power and phase-locking indices were associated with working memory deficits. Conclusions . The observed results confirm the applicability of aeGBR disturbances as a stable endophenotype of schizophrenia, and suggest a cognitive, rather than sensory, deficit at their origin.